Ethical and juridical implications relating to surrogate pregnancy. An overview from a european perspective - Emaldi Cirión, Aitziber (Acta Bioethica, 2017)
We find ourselves in a time of far reaching biotechnological breakthroughs and alongside with this, society is also experiencing changes. In this sense, new regulations regarding homosexual marriage have opened an scenario where same sex couples of men or women, may “procreate”, not only by means of adoption – not permitted for homosexual couples in many countries – but also through in vitro fertilization. For this reason, surrogate pregnancy is becoming the option of choice enabling heterosexual couples with specific problems, male couples, and males without a female partner to have a child. Indeed, as surrogate pregnancy techniques proliferates, ethical conflicts arise: the possibility of men to have their own children, problems relating filiation, instrumentalization of women and babies, legal solutions given by different European countries. In this article, both bioethical and legal issues regarding surrogate pregnancy will be analyse looking for the best interest of the minors.